3-Substituted Quinolines as RORγt Inverse Agonists. Issue 12 (15th June 2019) - Tanis, Virginia M.; Venkatesan, Hariharan; Cummings, Maxwell D.; Albers, Michael; Kent Barbay, J.; Herman, Krystal; Kummer, David A.; Milligan, Cynthia; Nelen, Marina I.; Nishimura, Rachel; Schlueter, Thomas; Scott, Brian; et al.
Graphical abstract: We have previously reported the syntheses of a series of 3, 6-disubstituted quinolines as modulators of the retinoic acid receptor-related orphan receptor gamma t (RORγt). These molecules, such as 1, are potent binders but are high molecular weight and they exhibited poor solubility at pH 2 and pH 7. This manuscript details our efforts at improving physical chemical properties for this series of compounds by increasing the diversity at the 3-position ( i.e. introducing heteroatoms and lowering the molecular weight). These efforts have led to molecules such as 27 and 30 which are potent binders with improved solubility. Abstract: We have previously reported the syntheses of a series of 3, 6-disubstituted quinolines as modulators of the retinoic acid receptor-related orphan receptor gamma t (RORγt). These molecules are potent binders but are high molecular weight and they exhibited poor solubility at pH 2 and pH 7. This manuscript details our efforts at improving physical chemical properties for this series of compounds by increasing the diversity at the 3-position ( i.e. introducing heteroatoms and lowering the molecular weight). These efforts have led to molecules which are potent binders with improved solubility.